A Conceptual Priority Index for Purchasing Medical Equipment in Hospitals. Issue 3 (July 2015) - Saleh, Neven; Sharawi, Amr A.; Wahed, Manal Abdel; Balestra, Gabriella
<x xml:space="preserve">Abstract</x> Many hospitals do not have a well-planned process to prioritize purchasing requests. Obviously, this problem is due to the lack of a fair evaluation of the requirements as well as absence of the cooperation of the hospital management staff. Therefore, it is essential to have a systematic and a comprehensive acquisition program to prevent a number of potential problems. This article presents a solution for the prioritization problem of purchasing requests of medical equipment by adopting a framework that combines Quality Function Deployment with Fuzzy logic system. The validation of the proposed model was carried out on 20 requests for purchasing medical equipment in a public hospital. The results indicate that the Quality Function Deployment-Fuzzy method can efficiently address the priority of requests considering a wide range of criteria. In addition, it can also provide the stability of process assurance.